Analyse Genotypique De La Contribution De La Matiere Assimilée Du Pedoncule Dans Le Remplissage Du Grain Chez Le Ble Dur (Triticum Durum D.E.S.F.) - Kahali, Linda; Djekoun, Abdelhamid (European Scientific Journal, ESJ, 2016)
In a part of study on morpho-physiological characterization in durum wheat; we were interested in quantifying the stem dry matter produced after anthesis and its contribution in the grain filling. When the climatic conditions are unfavorable ; the photosynthetic activity of the post-anthesis is reduced. The plant then uses the assimilates stored in the stem to increase its filling rate of grain. Thus, the behavior of four varieties of durum wheat is analyzed in the field using different parameters: (i) relative water content (RWC) of the flag leaf (ii) dry weight development of the grains (iii) peduncle assimilated dry matter contribution in the grain filling. The leaf water status, appreciated by measuring the RWC, is an indicator of the photosynthetic apparatus functioning. The measured values showed a significant difference between two agricultural companions. The results also showed a genotypic difference in the dry matter accumulation in the grains, mainly related to its filling speed. The accumulation of assimilates in the peduncle during the days following flowering, constitutes an advantage of reserves in dry matter before installation of water deficit. Indeed, it affects production by decreasing the photosynthetic activity. In conclusion, this experiment has highlighted two types of grain yield elaboration of cultivated wheat in the post-anthesis water deficit conditions.